KAJIAN PENGGUNAAN CUBICOST UNTUK PEKERJAAN QUANTITY TAKE OFF PADA PROSES TENDER - Anindya, Ajeng Ayu; Gondokusumo, Onnyxiforus (Universitas Tarumanagara, 2020)
The short duration of the tender process causes the time to do quantity take off for rebar is also short. This needs innovation to speed up the quantity take off for rebar in the tender process. The technological developments can be utilized to speed up quantity take off for rebar, one of that is Building Information Modeling (BIM). One of the BIM's that can be used to do quantity takeoff for rebar is